Analisis risiko kesehatan akibat pajanan timbal (Pb) dalam biota laut pada masyarakat sekitar Teluk Kendari - Muhamad Syarifuddin; Sarto Sarto (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Analysis of health risk due to lead (Pb) exposure in marine biota on the community around Kendari BayPurpose: To understand the risk level of health problem because of the lead exposure found on fish and shellfish that was consumed by community around Kendari bay.Methods: This study was an analytical observational through a cross sectional study design by combining Environmental Health Risk Analysis (ARKL) and Environmental Health Epidemiology (EKL) approaches. Population around Kendari bay was taken using proportional sampling criteria. The marine biotas in this study were 30 fish samples of 3 kind of most consumed fish and shellfish from 6 fishponds in Kendari bay. Measurement of lead content on it was made by Atomic Absorption Spectrometry (AAS).Results: The results of the study shows the lead content on fish and shellfish were 0,0027-0,0095 mg/kg and 0,1026-0,1097 mg/kg respectively while intake rapidity of fish and shellfish 0,0051 mg/kg/day and 0,016 mg/kg/day respectively. Health risk level of consuming contaminated fish was 1.29 while the contaminated shellfish was 4.03.Conclusions: The community around Kendari Bay has a risk of health problems (RQ> 1) due to lead exposure, therefore it needs to be controlled.